Hubungan Celebrity Worship dengan Implusive Buying Merchandise pada Penggemar JKT48 di Kota Jambi - Khairunisa Fitriya Kusuma; Fadzlul Fadzlul; Rion Nofrianda; Annisa Andriani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
This study aims to examine the relationship between celebrity worship and impulsive buying among JKT48 fans in Jambi City. The phenomenon of strong emotional attachment to idols is believed to influence fans’ consumption behavior, including the tendency to make spontaneous merchandise purchases without careful planning.This study employs a quantitative approach with a correlational design. The study population consists of JKT48 fans residing in Jambi City. The sampling technique employed purposive sampling, with respondents meeting the following criteria: aged 17–25 years, active as JKT48 fans, and having previously purchased JKT48 merchandise. The research instruments included the Celebrity Attitude Scale (CAS) to measure celebrity worship and the Impulsive Buying Scale to measure the tendency toward impulsive buying. Data analysis was conducted using the Pearson Product-Moment correlation test.The results indicate a relationship between celebrity worship and impulsive buying among JKT48 fans in Jambi City. The higher the level of celebrity worship, the higher the tendency toward impulsive buying of JKT48 merchandise. Conversely, the lower the level of celebrity worship, the lower the fans’ tendency toward impulsive buying. Based on the research findings, it can be concluded that celebrity worship is associated with impulsive buying among JKT48 fans in Jambi City. These findings indicate that emotional attachment to idols is one of the factors that contribute to impulsive buying behavior among fans.